2016
DOI: 10.1093/brain/aww042
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin is a candidate preventive medicine against amyloid-β and tau oligomers

Abstract: Amyloid-β, tau, and α-synuclein, or more specifically their soluble oligomers, are the aetiologic molecules in Alzheimer's disease, tauopathies, and α-synucleinopathies, respectively. These proteins have been shown to interact to accelerate each other's pathology. Clinical studies of amyloid-β-targeting therapies in Alzheimer's disease have revealed that the treatments after disease onset have little benefit on patient cognition. These findings prompted us to explore a preventive medicine which is orally avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 71 publications
2
110
0
2
Order By: Relevance
“…Increased oxidative stress at initial stages of neurotoxic conditions is also associated with activation of autophagylysosomal system [55,56] that could be beneficial and protective per se. Meanwhile, Pickford et al have shown decreased autophagy in addition to accelerated Ab aggregation in the brain of mice model of AD [57].…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress at initial stages of neurotoxic conditions is also associated with activation of autophagylysosomal system [55,56] that could be beneficial and protective per se. Meanwhile, Pickford et al have shown decreased autophagy in addition to accelerated Ab aggregation in the brain of mice model of AD [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose of rifampicin significantly influenced SUVR change in multiple regression analysis in Group B (Table 3). The oral administration of 1.0 mg/day was more effective than 0.5 mg/day in a mouse model, indicating a dose-dependent effect of rifampicin on AD pathology [8]. A dose of 300 mg/day has little effect on mild-to-moderate AD [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of the preventive effect of rifampicin on the pathological process of AD was thoroughly investigated in vitro [18] and in vivo [8, 19]. According to these studies, rifampicin has a versatile action to prevent the pathological process of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations